Infection capacity of Trypanosoma vivax experimentally inoculated through different routes in bovines with latent Anaplasma marginale - Bastos, Thiago Souza Azeredo; Faria, Adriana Marques; Cavalcante, Alliny Souza de Assis; Madrid, Darling Melany de Carvalho; Zapa, Dina Maria Beltrán; Nicaretta, João Eduardo; Cruvinel, Leonardo Bueno; Heller, Luciana Maffini; Couto, Luiz Fellipe Monteiro; Rodrigues, Daniel de Castro; Ferreira, Lorena Lopes; Soares, Vando Edésio; et al. (Elsevier, 2020)
The aim of the present study was to compare the infection capacity of Trypanosoma vivax experimentally inoculated through different routes in calves naturally infected with latent Anaplasma marginale. On Day 0 of the study, 25 calves (breed: Girolando) were divided into five groups. The first four groups of five calves each received approximately 1 × 106 trypomastigotes of T. vivax through the intradermal, subcutaneous, intramuscular and intravenous routes. Another five animals remained unaffected to serve as A. marginale naturally infected controls. The study of T. vivax was performed on all calves from D+1 to D+30 using the Woo, Brener and blood smear techniques. PCR was performed on Days +1, +3, +4, +5, +28, +29 and + 30. The results indicated that T. vivax was capable of infecting and developing the disease in the calves independent of the inoculation route. A positive correlation was found between T. vivax and rectal temperature (P ≤ 0.05) and a negative correlation was seen between the protozoan and globular volume (P ≤ 0.05). Latent A. marginale in the calves acted as co-infection for T. vivax. Jaundice was seen only in calves with a high parasitemia by A. marginale. Therefore, in areas with the confirmed presence of T. vivax in bovines, this protozoan should be included in the complex denominated “Bovine Parasitic Sadness”, which currently encompasses only Anaplasma and Babesia.
Keywords: Anaplasmosis; Bovine parasitic sadness; Trypanosomosis